Pengaruh bahasa Jawa dalam pembauran kod golongan muda Melayu berketurunan Jawa - Pawit, Mohammad Firdaus; Sheik Said, Normahdiah (Institute of the Malay World and Civilisation, Universiti Kebangsaan Malaysia, 2014)
This study was conducted to review and assess the extent of the use of the Java language that gives rise to code diffusion phenomena in speech among young people. This study investigates the extent to which the Java language practiced by young people of Javanese descent in kampung Sungai Leman, Sekinchan, Selangor. The authors also explore the places that are normally frequented by young people to speak Javanese and present examples of mixed Javanese and Malay languages in everyday conversation. This study was carried out using in-depth interviews and questionnaire survey. The questionnaire survey was conducted on 40 young respondents aged 6 to 25 years. Results of the study show that the young people in the lower category are not able to master the Java language and thus resulting in their mixing of the Java language and Malay language in communication. If this phenomenon is prolonged it is feared that it will result in language usage errors, both Malay or native language. This research is important in order to provide assurance that the Malay language continues to be further emphasized and that the Java language is preserved by the native speakers. In conclusion it is imperative that the use of Java language influences the code diffusion phenomena in the Malay language.